APPLICATION OF INTELLIGENT SYSTEMS (DEEP LEARNING) TOWARDS THE USE OF AI APPLICATIONS IN DAILY LIFE (PANCABUDI UNIVERSITY MEDAN) - Ardiansyah; Aldy Agustian; Perianus lombu; Kiki Wulandari; Muhammad Syahputra Novelan (RADJA PUBLIKA, 2025)
As technology advances in this digital era, technology has become a very important thing for human life and has a dependency, marked by the use of digital machines that cause very rapid, significant changes to all sectors of human life, making it easier for humans to carry out activities and have dependencies. Artificial intelligence or better known as AI (Artificial Intelligence) is a major supporter in the development of intelligent systems (Intelligence Systems) that increase efficiency and innovation in various sectors of life. Therefore, the latest advances in AI's predictive capabilities can create a productive work environment. Although AI offers great potential to encourage innovation and better decision-making, there are also challenges in the use of AI such as ethical issues, data security, and infrastructure limitations that must be overcome to ensure responsible use.